DIAGNOSTICS OF STUDENTS' LEARNING DIFFICULTIES IN MATHEMATICS SUBJECTS AT STATE 61 PRIMARY SCHOOL BANDA ACEH - Fajria, Nola; Sari, Siti Mayang (SENSEI RESEARCH CENTER, 2024)
Diagnostics of learning difficulties is one way that can be used to study and understand the problems experienced by students in teaching and learning activities. This research aims to determine students' learning difficulties, especially in mathematics subjects and the factors that cause them. This research is included in the descriptive research type using a quantitative approach. The population of this study were students at SDN 61 Banda Aceh consisting of 164 people. Meanwhile, the research sample was 18 class IV students. The data collection technique used was DCM (Problem Checklist) and analyzed using descriptive percentage techniques. The results of the research show that every student has obstacles and problems that can be identified as difficulties learning mathematics at school, both in terms of (1) Internal factors caused by; 45% Study Habits, 97% Interest, 80% Motivation and (2) External factors which include; 46% school environment and 25% family environment.